Workshop Pembelajaran Mendalam Dan Manajemen Kelas Untuk Meningkatkan Kompetensi Guru SD Islam Ali Bin Abi Thalib - Ilham Handika; Lalu Wira Zain Amrullah; Asri Fauzi; Aisa Nikmah Rahmatih (Educational Consultant & Counseling Career (EC3) Mataram, 2026)
This community service activity aims to improve teachers' pedagogical competence through a workshop on deep learning and classroom management at Ali Bin Abi Thalib Islamic Elementary School. The background to this activity is based on teachers' limited understanding of the implementation of deep learning and the suboptimal application of classroom management strategies in the learning process. This condition results in learning still tending to be teacher-centered and not fully encouraging active student engagement and critical thinking skills. The implementation method consisted of preparation, workshop implementation, learning simulations, practical development of learning materials, and activity evaluation. The workshop was conducted using lectures, discussions, simulations, and mentoring methods. The results showed an increase in teachers' understanding and skills in implementing deep learning and effective classroom management strategies. Teachers were able to design more active, reflective, and student-centered lessons. Furthermore, participants responded positively to the workshop because the material provided was relevant to the learning needs of elementary schools. Therefore, the workshop on deep learning and classroom management can be one way to improve teachers' pedagogical competence and the quality of learning in elementary schools